Information tasks toward a user-centered approach to information systems - Allen, Bryce (Academic Press, 1996)
The user-centered approach is central to the creation of usable information systems, services, and institutions. Information system design should derive from user research into information needs, tasks accomplished in meeting those needs, and resources used in the tasks. Information Tasks summarizes user research, then presents design sketches of systems that illustrate how design is linked to research. Also discussed are usable information services and an overview of the organization and economics of information institutions. This comprehensive user-centered approach provides an agenda for information research, design, and education that challenges many accepted beliefs and suggests new directions for information work. Information Tasks is of interest to library and information science students and faculty interested in information storage and retrieval, user studies, and systems analysis design. Students and scholars of human factors in systems design, human-computer interaction, and cognitive engineering also find the text useful. It reviews user research from many disciplines, and links research to practical design issues. It provides a unified model for user studies and user-centered design, and includes how-to summaries of design chapters. It shows how designers can investigate their user communities. It provides a general template for the design process. It integrates all aspects of information design, and discusses library issues in the larger information context.
Keywords: User interfaces (Computer systems); System design.; Information storage and retrieval systems.; Computers -- System Administration -- Storage & Retrieval.; Technology & Engineering -- Engineering (General).; Automation of library & information processes.; elektronické knihy; electronic books